The Spiral of Innovating and Digitalizing: Innovation Shaped by Past Digitalization and Shaping Intention to Adopt New Digital Technology - Samsami, Mahsa; Schøtt, Thomas (Senate Hall, 2022)
Digital technology in a firm enhances its capabilities and thereby may promote its innovation. In turn, innovation, for its full development and marketing, may benefit from adoption of new digital tools. Thereby the relationship between digitalizing and innovating can plausibly be hypothesized to be an ongoing reciprocal coupling, that over time may spiral upward in competitive firms and downward in others. Reciprocity is analyzed with a survey in 2021 of a globally representative sample of 30,939 firms around the world, asking about their current innovation, antecedent digitalization, and intended future digitalization. Past and especially recent digitalization are found to promote product innovation and particularly process innovation in a firm. In turn, product innovation, and especially process innovation, are promoting intention to adopt new digital technology in the near future. Findings contribute to accounting for the coupling between digitalizing and innovating as a spiral that is ongoing and weak, but mutually reinforcing.
Keywords: digitalization|innovation|adoption of technology|dynamic capability|firms